2017
DOI: 10.1246/cl.160834
|View full text |Cite
|
Sign up to set email alerts
|

Guest Binding and Catalysis in the Cavity of a Cubic Coordination Cage

Abstract: Mike Ward studied in Cambridge for his BA and Ph.D. before a post-doc position in Strasbourg with Jean-Pierre Sauvage. His independent academic career started with a lectureship in Bristol from 1990, and he remained there for 13 years before moving to Sheffield as a Professor of Inorganic Chemistry in 2003. His research interests cover many aspects of transition-metal and lanthanide ion coordination and supramolecular chemistry.Chris Hunter is the Herchel Smith Professor of Organic Chemistry at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“… 4 As part of our work in this area using an octanuclear cubic M 8 L 12 cage ( Fig. 1 ), 5 we have demonstrated that the accumulation of counter-ions around the exterior surface of a cationic cage is just as important a phenomenon as the binding of neutral guest molecules inside the cavity. 6–10 This is a conclusion that has also been reached by others who have demonstrated how interactions of metal/ligand cage assemblies with counter-ions at the exterior surface can play fundamentally important roles in controlling structure and speciation behaviour of cage assemblies, as well as their ability to bind guests in the central cavity.…”
Section: Introductionmentioning
confidence: 84%
“… 4 As part of our work in this area using an octanuclear cubic M 8 L 12 cage ( Fig. 1 ), 5 we have demonstrated that the accumulation of counter-ions around the exterior surface of a cationic cage is just as important a phenomenon as the binding of neutral guest molecules inside the cavity. 6–10 This is a conclusion that has also been reached by others who have demonstrated how interactions of metal/ligand cage assemblies with counter-ions at the exterior surface can play fundamentally important roles in controlling structure and speciation behaviour of cage assemblies, as well as their ability to bind guests in the central cavity.…”
Section: Introductionmentioning
confidence: 84%
“…Inspired by the ultimate enzyme catalyst 1,2 , supramolecular catalytic systems seek to be biomimetic 3,4,5 for features such as presence of an active site 6 with optimized non-covalent interactions with the substrate, 7 electrostatic preorganization that eliminates the reorganization cost paid by the uncatalyzed reaction, 8,9 as well as desolvation and dynamical effects that are relevant for the complete catalytic cycle. 10,11,12 In turn, the weak intermolecular interactions that govern supramolecular assemblies offer the undeniable advantage of easy functionalization, reversibility, and fast self-assembly 5,13,14 that overcome limitations of a delicate and more difficult redesign of an enzyme scaffold 15 . Supramolecular catalysts have the potential to revolutionize the chemical industry by allowing simpler and more flexible reaction pathways that offers lower cost, reduces the creation of undesired byproducts 16,17,18,19 , operates in a broad range of conditions.…”
mentioning
confidence: 99%
“…104 − 106 Coordination cages as preformed crystalline matrices have recently been used for host–guest studies consistent with the crystalline sponge method. 107 When Ward et al encountered difficulty in obtaining host–guest structures using a [Co 8 L 12 ](BF 4 ) 16 cage with naphthyl-based bis-bidentate bridging ligands via cocrystallization, they used preformed crystals of the cage for soaking, 108 where neat cycloundecanone (with minimal MeOH to prevent crystal desolvation) was trapped and observed. Other studies with a similar cage led to the observation of adamantane-1-carboxylic acid and alkyl-phosphonate chemical warfare agent simulants via SC-XRD.…”
Section: Diversity Of Crystalline Matricesmentioning
confidence: 99%
“…For Co-based cage synthesis, upon performing a one-step synthesis of the bis-bidentate ligand, crystals can be conventionally grown in 7 d or in 12 h via a solvothermal method yielding higher-quality larger crystals. 112 , 113 Soaking experiments for MOPs have been reported in as short as a few minutes versus 2–4 d reported with MOFs, 107 providing another potential benefit of using MOPs.…”
Section: Diversity Of Crystalline Matricesmentioning
confidence: 99%